A future for Kiribati. New models for resilient housing settlements - Firrone, Tiziana; Bustinto, Carmelo (Gangemi, 2023)
According to the Special Report on the Ocean and Cryosphere in a Changing Climate, the sea level has grown at a rate of 3.6 mm per year in the period between 2005 and 2015, increasing faster over the last century due to the melting of ice caps and the thermal expansion of the ocean. This increases the risks for populations living in coastal areas and in particular for those living in arctic regions and in the atolls, like the islands of Kiribati which, by the middle of the century, could become uninhabitable. The coastal protection systems and the adaptation processes that use ecosystems and solutions derived from nature (ecosystem-based adaptation), foresee rather long realization times and the population of Kiribati runs the risk of being forced to move elsewhere in a short time. From these premises, the study conducted at the Department of Architecture of the University of Palermo takes its cue, aimed at identifying new housing models capable of facing imminent emergencies and avoiding the abandonment of the lands of origin. Sustainable housing solutions, designed in accordance with the local settlement tradition and able to satisfy the needs of a community that, although not having no role in the production of greenhouse gases, it must adapt to the new environmental conditions imposed by industrial development policies from which it is totally foreign.